2022
DOI: 10.3389/fpsyt.2022.913902
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 pandemic on the well-being of children with autism spectrum disorder: Parents’ perspectives

Abstract: The COVID-19-related lockdown interrupted children’s learning progress and discontinued social learning and regular activities that children with autism spectrum disorder (ASD) rely on socially and physically. Negative consequences for children with ASD were reported far and wide. To investigate this problem in Kazakhstan, we conducted a mixed-methods study that drew on data from an online survey with 97 parents and semi-structured interviews with 14 parents. While parent-report quantitative results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…Different from the findings in the present study, a survey carried out by Amirova, A. et al, identified that all parents unanimously were against online learning, in addition to showing that parents were forced to deal with the various responsibilities imposed without having adequate training, generating an increase in stressors during the pandemic period 15 .…”
Section: Remote Teaching and Children/adolescents With Asdcontrasting
confidence: 99%
“…Different from the findings in the present study, a survey carried out by Amirova, A. et al, identified that all parents unanimously were against online learning, in addition to showing that parents were forced to deal with the various responsibilities imposed without having adequate training, generating an increase in stressors during the pandemic period 15 .…”
Section: Remote Teaching and Children/adolescents With Asdcontrasting
confidence: 99%
“…Parents of these children were already experiencing high parental stress before the pandemic [10,11], so the impact of the COVID-19 crisis might be less severe than in the general population because of a ceiling effect. In addition, some aspects of parenting stress, such as stress related to school avoidance or peer con icts, may be attenuated during lockdowns [12]. However, our main hypothesis is that parenting stress became even more severe among parents with a child who was already receiving treatment for a mental health problem, which further negatively impacts their child's mental health.…”
Section: Introductionmentioning
confidence: 90%
“…The study furthered that individuals with ASD expressed that their needs were not adequately addressed because of lockdown measures, i.e., they experienced difficulties in accessing essential healthcare services and facilities. Other studies (see Amirova et al, 2022;Pachner & Aranyi, 2021;Mutluer et al, 2020) also substantiate that the pandemic was likely to have negative effects on children with ASD because it disrupted educational services. It has also been reported that the lockdowns caused them to lose their previously acquired skills (Amorim et al, 2020).…”
Section: Introductionmentioning
confidence: 95%